CD8+ T cells promote cytokine responses to stress. (January 2019) - Clark, Sarah M.; Song, Chang; Li, Xin; Keegan, Achsah D.; Tonelli, Leonardo H.
Highlights: Depletion of CD8 + T cells in wild type mice abrogates cytokine responses to repeated foot-shocks. T cell deficient mice have an attenuated cytokine response to repeated foot-shocks. T cell deficient mice reconstituted wit CD8 T cells display enhanced cytokine responses to repeated foot-shocks. Abstract: Psychological stress is known to have profound effects on immune function and to promote inflammatory conditions. Elevated circulating levels of cytokines associated with stress are known to increase the risk to several diseases, but little is known about this mechanism. This study assessed the role of T cells on cytokine levels after exposure to stress in the learned helplessness paradigm. Adoptive transfer of CD4 + T cells into Rag2 −/− mice did not change cytokine levels to stress while CD8 + T cells resulted in an increase in TNF-α, IL-6 and IFN-γ in stressed Rag2 −/− mice. Moreover, depletion of CD8 + T cells in WT mice abolished these cytokine responses to stress. Corticosterone and behavioral stress responsiveness was impaired in Rag2 −/− mice reconstituted with CD8 + T cells. Notably, depletion of these cells in WT mice had no effect on behavior or corticosterone levels. Exposure to stress did not change the expression of canonical markers of T cell activation including CD62L and CD44 or modified intracellular cytokine content, suggesting that they are not the main producers of circulating cytokines in response to stress. These results show that CD8 + T cells promote TNF-α, IL-6 and IFN-γ responses to stress, possibly by stimulating non-lymphoid cells.